Learning and adaptation for forest conservation - Sayer, Jeffrey A. (CRC Press, 2001)
The past three decades have seen significant investments in programs to protect forests in developing countries. As a result the number and aggregate area of National Parks and equivalent protected areas have grown considerably. But a recent report released by WWF/World Bank has concluded that only small proportion of these areas is under secure and effective conservation management. There is a clear mismatch between the high-level global commitment to nature conservation as manifested in the Convention for Biological Diversity and the lack of concrete conservation achievement in the field. This chapter draws upon the author's personal experience as a manager of conservation programs in tropical Africa and Asia. The author's first project in the late 1960s in Zambia may have been the first to use the term integrated conservation and development. As we enter the 21st century, approaches to conservation have come to be based on engagement with, and participation by, people living in and around protected areas. There is no "best outcome" for conservation. Conservation has to adapt continuously as people's conditions and aspirations change and as nature itself evolves. The hypothesis of this chapter is that, although the conceptual framework for achieving conservation is now stronger, the institutions responsible for management are still dominated by a command-and-control culture that they have inherited from the past. The chapter therefore explores some of the organizational changes that are required if management of conservation forests is to be genuinely collaborative and truly adaptive.